Enhanced airport security screening under fermatean probabilistic hesitant fuzzy hybrid aggregation information - Wania Iqba; Shahziab Ashraf; Maria Akram; Muhammad Shazib Hameed (Big Data and Computing Visions)
Optimizing airport security screening processes is imperative in the modern age, ensuring a delicate balance between stringent security measures and efficient, seamless travel experiences for passengers. This research presents an innovative paradigm for decision-making that optimizes airport security screening procedures. By utilizing sophisticated fuzzy concepts, particularly Fermatean Probabilistic Hesitant Fuzzy Sets, the research presents new hybrid aggregation techniques known as Fermatean Probabilistic Hesitant Hybrid Weighted Averaging FePHHWA and Hybrid Weighted Geometric FePHHWG. These procedures are intended to improve the decision-making process by providing a thorough method of addressing the intricacies of security screening. In addition to showcasing the flexibility and effectiveness of Fermatean Probabilistic Hesitant Fuzzy Sets, the suggested technique creates a strong foundation for resolving issues with airport security screening by utilizing the recently developed hybrid aggregation processes.